Heidegger’s Gelassenheit, Daoist Wuwei 無為, and Non-willing - BURIK, Steven (Institutional Knowledge at Singapore Management University, 2024)
This article explores a key notion of Classical Daoism, namely wuwei 無為, through the lenses of Martin Heidegger’s Gelassenheit. My aim is to ask the question of whether a Heideggerian reading allows us to understand wuwei as a notion that circumvents the subject-object distinction characteristic of the Western metaphysical tradition. That distinction is, according to Heidegger, representative of the obsession in Western thought to “represent” (Vorstellen; literally to “put in front”) things. In other words, I will argue that Heidegger provides us with a possibility to challenge and escape the dominance of metaphysics as representational thinking, and that Heidegger’s challenge may allow us a clearer understanding of wuwei in Daoism, by asking if the conceptual move made through wuwei is similar of that made with Heidegger’s Gelasssenheit. To do this I will investigate wuwei based on ideas of willing and non-willing, found in both Heidegger and Daoism.